Modeling the hydrodynamic wake of an offshore solar array in OpenFOAM - van der Eijk, Martin; Plenker, Désirée; Hendriks, Erik; de Wit, Lynyrd (Frontiers in Energy Research, 2024)
Offshore solar is seen as a promising technology for renewable energy generation. It can be particularly valuable when co-located within offshore wind farms, as these forms of energy generation are complementary. However, the environmental impact of offshore solar is not fully understood yet, and obtaining a better understanding of possible impact is essential before this technology is applied at a large scale. An important aspect which is still unclear is how offshore solar affects the local hydrodynamics in the marine environment.This article describes the hydrodynamic wake generated by an offshore solar array, arising from the interaction between the array and a tidal current. A Computational Fluid Dynamics (CFD) modelling approach was used, applying numerical Large Eddy Simulations (LES) in OpenFOAM.The simulations are verified with the numerical model TUDFLOW3D. The study quantifies the wake dimensions and put them in perspective to the array size, orientation, and tidal current magnitude.The investigation reveals that wake width depends on array size and array orientation. When the array is aligned with the current, wake width is relatively confined and does not depend on the array size. When rotated, the wake width experiences exponential growth, becoming approximately 30% wider than the array width. Wake length is influenced by factors such as horizontal array dimensions and current magnitude. The gaps in between the floaters decrease this dependency. Similarly, the wake depth showed similar dependencies, except for the current magnitude, and only affects the upper meters of the water column. Beneath the array, flow shedding effects occur, affecting a larger part of the water column than the wake. Flow shedding depends on floater size, gaps, and orientation